Analysis of Phonological Errors in Description Texts of Grade IV Elementary School Students in SDN 1 Panjang - Azka, Milati; Faiqaturrasyidah; Ufa Uli Aulia; Rani Setiawaty (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to examine (1) forms of language errors at the phonological level in fourth-grade students at SDN 1 Panjang and (2) factors that cause language errors. The type of research used is a qualitative method with a narrative approach (data description). This research data is in the form of descriptive text, which contains phonological errors. Data collection techniques include observation, interviews, and documentation. The data analysis technique uses the agih method, which involves replacing and reading markers. Based on the results of this research, it was found that there were still language errors at the phonological level in students' descriptive essays. Errors found include adding phonemes, subtracting phonemes, and changing phonemes. Second, factors causing phonological errors experienced by 6 class VI students at SDN 1 Panjang include the influence of the learning process that is being studied or has been studied, students' lack of understanding of a particular language, the impact of the surrounding environment, and habits that do not support good language use and actual.